Literary and Historical Foundations of the Zullisanayn Tradition (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The phenomenon of bilingualism is also manifested in various forms in Sufi literature, which is considered the literary and historical foundation of the Zullisonayn tradition. In the early centuries of Islam, creativity in local languages ceased, and the Ajam peoples also engaged in science and creativity in Arabic. At the same time, they tried to save the spiritual heritage created in their native language from extinction by translating it into Arabic. In this sense, the cultural heritage created in Arabic is considered the common spiritual heritage of all Muslim peoples. The majority of Ajam poets and scholars who created in Arabic aimed to instill in their works the spiritual heritage left by their pre-Islamic thinkers. This article analyzes the data on the existence of scribes and scholars who were equally creative in two languages, and the existence of the Zullisonayn tradition not only among translators, but also among scribes and linguists.